P2Y6 and P2X7 Receptor Antagonism Exerts Neuroprotective/ Neuroregenerative Effects in an Animal Model of Parkinson’s Disease - Oliveira-Giacomelli, Ágatha; M. Albino, Carolina; de Souza, Hellio Danny Nóbrega; Corrêa-Velloso, Juliana; de Jesus Santos, Ana Paula; Baranova, Juliana; Ulrich, Henning (Frontiers in Cellular Neuroscience, 2019)
Parkinson’s disease is a neurodegenerative disorder characterized by decreased dopamine bioavailability in the substantia nigra and the striatum. Taking into account that ATP and its metabolites are intensely released in the 6-hydroxydopamine (6-OHDA) animal model of Parkinson’s disease, screening of purinergic receptor gene expression was performed. Effects of pharmacological P2Y6 or P2X7 receptor antagonism were studied in preventing or reversing hemiparkinsonian behavior and dopaminergic deficits in this animal model. P2X7 receptor antagonism with Brilliant Blue G at a dose of 75 mg/kg reestablished dopaminergic nigrostriatal pathway rats injured with 6-OHDA. Selective P2Y6 receptor antagonism by MRS2578 prevented dopaminergic neuron death in SH-SY5Y cells in vitro and in vivo in the substantia nigra of rats injured with 6-OHDA. Moreover, in vivo analysis showed that both treatments were accompanied by a reduction of microglial activation in the substantia nigra. Altogether, these data provide evidence that antagonism of P2X7 and P2Y6 receptors results in neuroregenerative and neuroprotective effects, respectively, possibly through modulation of neuroinflammatory responses.